CONCEPT OF CONSTRUCTION OF THE AUTOMATED WORKPLACE OF THE PSYCHOLOGIST OF THE NATIONAL GUARD OF UKRAINE - Bayda, M.; Horielyshev, S.; Kolesnichenko, O.; Prуkhodko I.; Chizhevsky, S. (Honor and Law, 2020)
The main trend in the automation of public activity management is the automation of planning and management functions on the basis of personal electronic computers installed directly at the workplaces of specialists. These systems are widely used in organizational management called workstations. The article discusses the modern understanding of the psychologist’s workstation as a component of the automated management system of the psychological service of the National Guard of Ukraine. The models of the organization and implementation of psychological work, the areas of psychological support, in accordance with which the psychologist forms his professional activity, the general content of the psychological work of the psychological support specialists of the National Guard of Ukraine are proposed. The content, structure and functionality of the psychologist’s workstation are proposed. A three-level hierarchical structure of the automated management system of the psychological service of the National Guard of Ukraine is proposed - the operational level, operational-tactical level, and tactical level. The types of automated workplaces of psychological service specialists at the tactical level (brigade level, regiment, separate battalion of the National Guard of Ukraine) are determined: deputy unit commander for work with personnel; head of the department of psychological support (head of the service of psychological support), senior officer (psychologist) of the department of psychological support, officer (psychologist) of the department of psychological support [executive officer (psychologist)]. The functional and technical requirements to the automated workplaces of psychological service specialists are formulated. The general structure of the workstation has been developed and the composition of the general and special software has been determined.